2017
DOI: 10.1097/pep.0000000000000362
|View full text |Cite
|
Sign up to set email alerts
|

Gait Training With Visual Feedback and Proprioceptive Input to Reduce Gait Asymmetry in Adults With Cerebral Palsy: A Case Series

Abstract: Outcome measures and training protocols were feasible in this sample of convenience of adults with CP who were ambulatory and who did not have visual impairment. The adults with CP in this study demonstrated individual improvements in gait and balance following training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…The hardware requirements and setup time of the IMU-based feedback platform are much lower than those for motion analysis systems 5 or virtual reality environments. 6 Our study demonstrated strong convergent validity of the IMU measurement with established optical motion capture measurement methods (the overall R 2 correlations approximating 1). The study indicated a greater rate of joint excursion for the IMU system than the optical system, and we believe that this is caused by movement of the IMUs relative to the overall limb segments because they overlie muscles which contract during gait.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The hardware requirements and setup time of the IMU-based feedback platform are much lower than those for motion analysis systems 5 or virtual reality environments. 6 Our study demonstrated strong convergent validity of the IMU measurement with established optical motion capture measurement methods (the overall R 2 correlations approximating 1). The study indicated a greater rate of joint excursion for the IMU system than the optical system, and we believe that this is caused by movement of the IMUs relative to the overall limb segments because they overlie muscles which contract during gait.…”
Section: Discussionsupporting
confidence: 61%
“…2 Some gait deviations in children with CP can persist and be recalcitrant to retraining even after pharmacologic or surgical management of spasticity and contracture. The potential for computational biofeedback modalities to augment gait retraining have been explored, [3][4][5][6][7][8] in recognition of the consistency and objectivity of feedback provided.…”
Section: Introductionmentioning
confidence: 99%
“…Young and older adults had reduced A/P and M/L tilt and A/P tilt velocity during normal walking ( 41 ). Cues have also been used to reduce knee adduction moments in people with knee osteoarthritis ( 42 ), alter plantar foot loading in people with stroke ( 43 ), and reduce gait asymmetry in people with cerebral palsy ( 44 ). When provided with combined auditory and vibrotactile SA, people with bilateral vestibular loss demonstrated decreased EMG amplitudes and less EMG background activity when standing on a compliant surface with their eyes closed ( 29 ).…”
Section: Real-time Use Findingsmentioning
confidence: 99%
“…Persons with compromised sensory systems (visual, vestibular, proprioceptive) may be able to use SA via a rehabilitation device to “upweight” ( 67 ) the available accurate information from the non-compromised system(s), or possibly enhance the “weakened signal” resulting in improved postural control. It appears that longer duration training with SA has better potential to enhance sensory reweighting ( 44 ). Persons with more severe sensory impairment have been found to benefit more from SA compared to those with moderate deficits, thus supporting the use of SA in acute stages of rehabilitation ( 47 ).…”
Section: Rehabilitation Using Augmented Sensory Feedbackmentioning
confidence: 99%
“…CP presents with positive and negative motor signs including: spasticity, weakness, impaired selective motor control and sensory deficits [4]. ICP has been used to improve balance [5], gait symmetry [6], upper limb strength [7] and other functional abilities in people with CP. Perhaps the largest study to date in this field is the 'Move it to improve it' (MITII) randomized controlled trial that used web-based therapy at home to improve occupational performance and visual perception in children with unilateral CP [8].…”
Section: Introductionmentioning
confidence: 99%